Ketika Aktor Damai Tidak Efektif: Respons Keuchik dan Tuha Peuet terhadap Konflik Pengelolaan APBG - Muhammad Sahlan; Muhammad Yunus Ahmad; Halik Halik (Sociology Department Of Syiah Kuala University, 2023)
The article addresses how the headman and the legislative members of the village in Aceh overcome issues in managing the village income and expenditure budget. Using a qualitative method, the article inductively analyzes the styles of the headman and the village legislature in dealing with issues regarding the village income and expenditure budget and examines the factors that influence their response styles. The data for this study consists of newspaper articles in local newspapers from 2014 to 2022. The findings identify two conflict resolution styles of headman and village legislature that are commonly used: unilateral action and seeking third-party intervention. Meanwhile, in the third style, measures for conflict resolution formulated through regulations do not feature in the newspaper reporting. Furthermore, the findings also identify some underlying causes for the conflict resolution styles that are used in this context, including mechanisms and actors. This study will contribute to the literature about post-conflict grassroot efforts in Aceh and formulate a more effective early warning system at the local level.AbstrakArtikel ini membahas tentang pola respons keuchik dan tuha peut terhadap konflik pengelolaan Anggaran Pendapatan dan Belanja Gampong (APBG). Dengan menggunakan pendekatan kualitatif, artikel ini menganalisa secara induktif bentuk-bentuk respons keuchik dan tuha peuet terhadap konflik pengelolaan APBG sekaligus mengkaji faktor-faktor yang mempengaruhi bentuk respons mereka. Data yang digunakan sebagai bahan analisis berasal dari pemberitaan surat kabar sejak 2014-2022. Studi ini mengidentifikasi dua model aksi yang paling sering digunakan oleh keuchik dan tuha peuet dalam konflik pengelolaan APBG, yaitu aksi unilateral (unilateral action) dan tindakan mencari bantuan intervensi pihak ketiga (third-party intervention). Sementara penyelesaian bersama (joint action) melalui langkah-langkah yang telah dirumuskan dalam sejumlah regulasi tidak muncul dalam pemberitaan surat kabar. Selain itu, studi ini juga mengidentifikasi faktor utama yang menyebabkan model penggunaan resolusi konflik tersebut, yaitu absurditas mekanisme dan peran pasif dan tidak efektifnya para aktor pendamping gampong